Overtopping Risk Analysis of Earth Dams considering Effects of Failure Duration of Release Structures - Lijun Liu; Zhenyu Wu (Complexity)
For modern high earth dams, sufficient safety margin is considered in the designs of flood discharge capacity and dam crest elevation to prevent flood overtopping. However, for high earth dams which may induce catastrophic consequences, during their long operational period, extremely hazardous scenarios which could occur and threaten dam safety need to be considered. For the earth dams located in areas with intensive seismicity, there is a possible scenario that the release structures fail due to seismic landslides and gate failures caused by a severe earthquake when the flood begins to enter the reservoir. Thus, it is desirable to investigate the influence of failure duration of release structures on dam overtopping risk. Based on the Bayesian network, a methodology for overtopping risk analysis of earth dams considering effects of failure duration of release structures is proposed. The overtopping risk of the PBG earth-rockfill dam was analyzed to illustrate the methodology. The critical release structures which dominate the dam overtopping risk are identified. The dam overtopping risk is most sensitive to the failure duration of the spillway. The tolerable failure duration of the spillway is approximately 3 days, and when the failure duration of the spillway reaches 4 days, the dam overtopping risk drastically rises to an unacceptable level. The case study suggests that the proposed methodology could be helpful to analyze the influences of possible failure durations of release structures on dam overtopping risk and could facilitate preparation for emergency plans.